Analgesics and anti-inflammatory medications in sports: use and abuse - Feucht, C. L.; Patel, D. R. (Pediatric Clinics of North America, 2010)
Both acute and overuse musculoskeletal injuries are common in adolescent athletes. Pharmacologic agents including nonsteroidal anti-inflammatory drugs, acetaminophen, and topical over-the-counter agents have been shown to be effective in controlling pain, but data regarding their efficacy in expediting healing and time to recovery continue to be debated. Studies indicate that adolescents consume analgesic agents on their own and may be unaware of their potential toxicities. Data also indicate that adolescent athletes use medications in hopes of alleviating pain and allowing continuation of sports without adequate time for healing. This article reviews the mechanisms, toxicity, drug interactions, efficacy, and abuse potential of commonly used analgesic and anti-inflammatory drugs.